Evidence Use in Health Policy Making An International Public Policy Perspective (Cham : Springer International Publishing, 2018)
This open access book provides a set of conceptual, empirical, and comparative chapters that apply a public policy perspective to investigate the political and institutional factors driving the use of evidence to inform health policy in low, middle, and high income settings. The work presents key findings from the Getting Research Into Policy (GRIP-Health) project: a five year, six country, programme of work supported by the European Research Council. The chapters further our understanding of evidence utilisation in health policymaking through the application of theories and methods from the policy sciences. They present new insights into the roles and importance of factors such as issue contestation, institutional arrangements, logics of appropriateness, and donor influence to explore individual cases and comparative experiences in the use of evidence to inform health policy. Justin Parkhurst is Associate Professor at the London School of Economics and Political Science (the LSE)'s Department of Health Policy, UK. He has conducted research on a range of global health policy issues and on the politics of evidence. He served as the Principal Investigator of the GRIP-Health programme of work. Benjamin Hawkins is Associate Professor at the Department of Global Health and Development, London School of Hygiene and Tropical Medicine, UK. His research focuses on the role of research evidence and corporate actors in health policy making. In addition, he works on European integration, multi-level governance international trade and political economy approaches to health policy. Stefanie Ettelt is Associate Professor at the Department of Health Services Research and Policy, London School of Hygiene and Tropical Medicine, UK. Her work examines the tensions between structure and agency in explaining the influence of evidence and research on policy-making and health system governance, particularly from a comparative perspective. .
Chapter 1: Studying evidence use for health policymaking from a policy perspective. Justin Parkhurst, Stefanie Ettelt, Benjamin Hawkins -- Chapter 2: The many meanings of evidence: A comparative analysis of the forms and roles of evidence within three health policy processes in Cambodia. Helen Walls, Marco Liverani, Kannarath Chheng, Justin Parkhurst -- Chapter 3: The role of evidence in nutrition policymaking in Ethiopia: institutional structures and issue framing. Helen Walls, Deborah Johnston, Elisa Vecchione, Abdulfatah Adam, Justin Parkhurst -- Chapter 4: The use of evidence in health policy in Ghana: implications for accountability and democratic governance. Elisa Vecchione and Justin Parkhurst -- Chapter 5: Using evidence in a highly fragmented legislature: the case of Colombia ́s health system reform. Arturo Alvarez & Benjamin Hawkins -- Chapter 6: The politics of evidence use in health policy making in Germany - the case of regulating hospital minimum volumes. Stefanie Ettelt -- Chapter 7: Electronic Cigarettes Regulation in the UK: A Case Study in Evidence Informed Policy Making. Dr. Benjamin Hawkins -- Chapter 8: Ministries of Health and the Stewardship of Health Evidence. Justin Parkhurst, Arturo Alvarez-Rosete, Stefanie Ettelt, Benjamin Hawkins, Marco Liverani, Elisa Vecchione, Helen Walls -- Chapter 9: Evidence use and the institutions of the state: The role of Parliament and the judiciary. Stefanie Ettelt -- Chapter 10: Evidence and Policy in Aid-Dependent Settings. Justin Parkhurst, Siobhan Leir, Helen Walls, Elisa Vecchione, Marco Liverani -- Chapter 11 - Conclusion: Reflecting on studying evidence use from a public policy perspective. Justin Parkhurst, Benjamin Hawkins, Stefanie Ettelt.
Political Science and International Studies
text file PDF
Keywords: Public policy; Political science; Legislative bodies; Medical policy; Welfare state